Limited Usefulness of 18F-FDG PET/CT in Predicting Tumor Regression After Preoperative Chemotherapy for Noncardia Gastric Cancer: The Italian Research Group for Gastric Cancer (GIRCG) Experience. (March 2020) - Morgagni, Paolo; Bencivenga, Maria; Colciago, Eleonora; Tringali, Domenico; Giacopuzzi, Simone; Framarini, Massimo; Saragoni, Luca; Mura, Gianni; Graziosi, Luigina; Marino, Elisabetta; Fumagalli Romario, Uberto; Baiocchi, Gianluca; et al.
Abstract : Background: The present study aimed to better define the usefulness of 18 F-FDG PET/CT in predicting pathological tumor response (PTR) and survival in patients with noncardia gastric cancer treated with preoperative chemotherapy. Methods: Seventy-one patients were recruited in 6 Italian centers. The SUV of 18 F-FDG PET/CT was measured at baseline and after treatment, and the difference (dSUV) was computed. The association between PET indexes and PTR, assessed by the Becker score, was evaluated by nonparametric regression. The discriminant power of PET indexes with respect to the absence of PTR (Becker 2/3) was studied by receiver operating characteristic (ROC) curve and synthesized by the area under the curve (ROC-AUC). Results: dSUV allowed to partially discriminate between absence/presence of PTR, when expressed as either absolute value (ROC-AUC, 0.73; 95% confidence interval, 0.59–0.87) or percentage (ROC-AUC, 0.74; 95% confidence interval, 0.59–0.89). However, only extreme values of percent dSUV were really informative. All 7 patients whose 18 F-FDG uptake had increased despite preoperative treatment showed no tumor regression at pathologic examination. Seven of the 10 patients whose metabolic response had been 70% or greater had complete or nearly complete pathologic tumor regression (Becker score 1a or 1b). The metabolic response of the remaining 54 patients, which ranged between 0% and 70%, did not permit to reliably forecast pathologic tumor regression. Survival significantly decreased with increasing Becker score but was unaffected by metabolic response. Conclusions: The present study suggests that 18 F-FDG PET/CT has limited usefulness in predicting cancer regression. The lack of metabolic response in serial measurements indicates the probable ineffectiveness of preoperative treatment. Abstract : Supplemental digital content is available in the text.